2014
DOI: 10.1007/s00276-014-1329-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the branching pattern of posterior division of mandibular nerve: a case report

Abstract: Such variant branches and communications between the branches of mandibular nerve as seen in this case have an embryological basis and are clinically important in this region especially for dental surgeries and anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…However, it may be premature to comment on the frequency of this variant due to the small sample size. This variable branch was also presented in a case reported by Muraleedharan et al [28], where numerous variations in the branching pattern of the posterior division of the mandibular nerve were presented. In the case report, the variant recurrent branch emerged from the left IAN and supplied the lateral pterygoid muscle.…”
Section: Discussionsupporting
confidence: 67%
“…However, it may be premature to comment on the frequency of this variant due to the small sample size. This variable branch was also presented in a case reported by Muraleedharan et al [28], where numerous variations in the branching pattern of the posterior division of the mandibular nerve were presented. In the case report, the variant recurrent branch emerged from the left IAN and supplied the lateral pterygoid muscle.…”
Section: Discussionsupporting
confidence: 67%
“…Before entering the mandibular foramen, the IAN gives rise to the nerve to mylohyoid. Communications between the IAN, lingual nerve (LN), hypoglossal nerve or the auriculotemporal nerve (ATN) have been reported [1][2][3][4][5]. The IAN is clinically important nerve, especially in dentistry so that inferior alveolar nerve blockade (IANB) is better understood [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (RODELLA, BUFFOLI, LABANCA et al, 2012) have shown that before entering the mandible, IAN can give multiple branches which are usually associated with accessory mandibular foramina and mandibular canals. Nevertheless, as reported by Muraleedharan, Veeramani and Chand (2014), in most cases where there are no associated accessory foramina, such branches innervate the LPM. In some cases this additional branch from IAN penetrates the LPM after supplying it to join the main trunk of mandibular nerve, its divisions or any of its branches.…”
Section: Discussionmentioning
confidence: 61%
“…Anatomical knowledge is essential for a diagnosis and treatment of maxillofacial disease. There are several explanations and suggest to anatomic variation, such as migration of neuroblasts and myoblasts in this area during embryogenesis (MURALEEDHARAN, VEERAMANI and CHAND, 2014).…”
Section: Discussionmentioning
confidence: 99%